2017
DOI: 10.1117/1.jbo.22.3.035007
|View full text |Cite
|
Sign up to set email alerts
|

Infrared microspectroscopic determination of collagen cross-links in articular cartilage

Abstract: , "Infrared microspectroscopic determination of collagen cross-links in articular cartilage," J. Biomed. Opt. 22(3), 035007 (2017), doi: 10.1117/1.JBO.22.3.035007. Abstract. Collagen forms an organized network in articular cartilage to give tensile stiffness to the tissue. Due to its long half-life, collagen is susceptible to cross-links caused by advanced glycation end-products. The current standard method for determination of cross-link concentrations in tissues is the destructive high-performance liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Histological analyses showed that PG and amide I concentrations predominantly increased while water content decreased as a function of cartilage depth (Figure 3). 30,33‐35 The differences between the distributions of collagen (amide I) and PG concentration between more (Mankin score > 5) and less degenerated samples (Mankin score ≤ 5) were not statistically significant.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Histological analyses showed that PG and amide I concentrations predominantly increased while water content decreased as a function of cartilage depth (Figure 3). 30,33‐35 The differences between the distributions of collagen (amide I) and PG concentration between more (Mankin score > 5) and less degenerated samples (Mankin score ≤ 5) were not statistically significant.…”
Section: Resultsmentioning
confidence: 92%
“…To (Figure 3). 30,[33][34][35] The differences between the distributions of collagen (amide I) and PG concentration between more (Mankin score > 5) and less degenerated samples (Mankin score ≤ 5) were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional methods for the determination of the degree of cross-linking in tissues include highperformance liquid chromatography (HPLC) and diffusion scanning calorimetry after enzymatic digestion of collected samples. However, both methods are time consuming, require sample blocks for analysis and are destructive preventing subsequent analysis with alternative techniques [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%